The Application of Optical Coherence Tomography Angiography in Cerebral Small Vessel Disease, Ischemic Stroke, and Dementia: A Systematic Review - Zhang, Jun-Fang; Wiseman, Stewart; Valdés-Hernández, Maria C.; Doubal, Fergus N.; Dhillon, Baljean; Wu, Yun-Cheng; Wardlaw, Joanna M. (Frontiers in Neurology, 2020)
Objective: To investigate the application of optical coherence tomography angiography (OCTA) in cerebral small vessel disease (SVD), ischemic stroke and dementia. Methods: We conducted a systematic search in Medline (from inception) and Embase (from 1980) to end 2019 for human studies that measured retinal parameters in cerebral SVD, ischemic stroke and dementia using OCTA. Results: Fourteen articles (n=989) provided relevant data. Ten studies included patients with Alzheimer’s disease (AD) and mild cognitive impairment (MCI) (n=679), two investigated pre-symptomatic AD participants (n=154) and two investigated monogenetic SVD patients with cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) (n=32) and Fabry disease (n=124). Methods to reduce bias and risk factor adjustment were poorly reported. Substantial methodological variations between studies precluded a formal meta-analysis. Quantitative measurements revealed significant yet inconclusive changes in foveal avascular zone, perfusion density and vessel density (VD) in AD, pre-symptomatic AD and SVD patients. Two (n=160) of three studies (n=192) showed association between decreased VD and increased white matter hyperintensities. In three (n=297) of seven studies (n=563), better cognitive function was associated with increased VD. One study (n=52) suggested increased VD was associated with increased ganglion cell-inner plexiform layer thickness in AD yet with no covariate adjustment. Conclusions: Changes in retinal microvasculature identified using OCTA are associated with monogenetic SVD and different stages of AD, but data are limited and partly confounded by methodological differences. Larger studies with risk factors adjustment and more consistent OCTA methods are needed to fully exploit this technology.